Determinasi penerimaan pajak daerah di Provinsi Aceh: Perspektif PDRB, inflasi dan investasi - Sulis Tia Wati; Iskandar Iskandar; Safuridar Safuridar (Nur Science Institute, 2025)
This study examines how gross regional domestic product (GRDP), inflation, and investment affect local tax revenue in Aceh Province. The analysis uses secondary time-series data from Statistics Indonesia (BPS) Aceh Province and the Directorate General of Fiscal Balance (DJPK) covering 2010–2024. Multiple linear regression was employed to test both the partial and joint effects of the independent variables on local tax revenue. The results indicate that GRDP and investment have positive, statistically significant effects on local tax revenue in Aceh, while inflation has a negative, statistically insignificant effect. Taken together, GRDP, inflation, and investment jointly influence local tax revenue. These findings suggest that strengthening regional economic activity and increasing investment are important levers for improving local tax revenue performance in Aceh. In addition, local governments should enhance tax administration, taxpayer compliance, and enforcement to ensure that gains in economic activity and investment translate more effectively into higher local tax receipts.